Change of Perspective, Change of Life - Rebecca, Ldouma (Journal of Anthropological Films, 2022)
Synopsis (English): The Oumarou family lived a nomadic way of life before settling on the outskirts of N’gaoundéré, in northern Cameroon. Change of Perspective observes how the family adapts to their new life by focusing on the activities of the wife, Hadjara, as she makes inroads to her new community and learns about health care options previously unavailable to nomadic people. Synopsis (French): La famille Oumarou a vécu un mode de vie nomade avant de s'installer dans la banlieue de N'gaoundéré, au Nord-Cameroun. Le film Change of Perspective montre comment cette famille s'adapte à sa nouvelle vie en se focalisant principalement sur les activités de l'épouse, Hadjara, alors qu'elle s’insère dans sa nouvelle communauté et opte pour des soins de santé auparavant inaccessibles aux nomades.